2020
DOI: 10.1007/s13691-020-00416-4
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of relapsed prostate small cell carcinoma with amrubicin: report of a case

Abstract: Standard therapy for metastatic small cell carcinoma of the prostate (SCCP) remains undefined. We have effectively treated relapsed SCCP with amrubicin. A 72-year-old patient, diagnosed with T4N1M0 prostate cancer, started hormonal therapy in May 2012, elsewhere, and his prostate-specific antigen levels remained low. However, pulmonary and hepatic metastases occurred; high neuron-specific enolase levels suggested SCCP, which was confirmed by repeated biopsy at our institution. In October 2016, chemotherapy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…El esquema de quimioterapia más efectivo para el tratamiento es la combinación cisplatino más etopósido, con una tasa de respuesta del 69% (10) , como se mostró en este caso. La asociación de doxorubicina no mejora la tasa de supervivencia (11) . Ya que la resolución es posible en la enfermedad limitada, se recomienda el tratamiento multimodal intensivo.…”
Section: Discussionunclassified
“…El esquema de quimioterapia más efectivo para el tratamiento es la combinación cisplatino más etopósido, con una tasa de respuesta del 69% (10) , como se mostró en este caso. La asociación de doxorubicina no mejora la tasa de supervivencia (11) . Ya que la resolución es posible en la enfermedad limitada, se recomienda el tratamiento multimodal intensivo.…”
Section: Discussionunclassified
“…AMR is an inhibitor of DNA topoisomerase II. A phase II trial demonstrated that AMR exerted significant activity against refractory or relapsed SCLC after platinumbased chemotherapy (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Second-line Systemic Therapy For Nepcmentioning
confidence: 99%
“…In a total of 12 NEPC patients, including 2 cases reported by our group, who had been treated with AMR were identified in the literature (23)(24)(25)(26)(27)(28). First-line therapies for these patients were etoposide plus platinum (N=10) and cisplatin plus irinotecan (N=2).…”
Section: Second-line Systemic Therapy For Nepcmentioning
confidence: 99%